Web Information System for E-Sport Arena Community with OWASP-Based Cybersecurity Using XP Method - Aufan, Afgha; Purwadi, Purwadi; Pritama, Argiyan Dwi (Journal of Information Systems and Informatics, 2025)
The rapid development of the e-sports ecosystem in Purwokerto has encouraged the emergence of digital communities such as the Esport Arena Community. However, the management of member data, event information, and merchandise transactions is still carried out manually through social media, resulting in inefficiency and limited-service reliability. This study aims to develop a web-based information system that integrates member management, jersey evolution documentation, and secure online merchandise transactions. The system was developed using the Extreme Programming (XP) method, which supports iterative development and continuous refinement. Security measures were implemented based on OWASP Top 10 recommendations, including prepared statements, input validation, CSRF protection, and Role-Based Access Control (RBAC). System evaluation using the System Usability Scale (SUS) produced a score of 88, categorized as Excellent, indicating high user satisfaction and strong usability performance. The results demonstrate that the system operates securely, reliably, and effectively improves operational efficiency for the Esport Arena Community.
Keywords: e-sports community, web information system, Extreme Programming, OWASP Top 10, cybersecurity, usability